Aktywność fizyczna polskich seniorów - Zieliński, Wojciech; Celka, Roman; Wojtkowiak, Tadeusz; Szyszka, Dorota (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The level of physical activity of the Polish seniors has been defined in accordance with Grimba’s scale of everyday activity. The examined people declared a level of activity in the past and present. The research was conducted in the period from 1999 to 2013. It involved 2494 respondents aged 65–103, including 1426 women and 1068 men – from all over Poland.The research results: The collected material was divided into 6 age groups, every 5 years. In all of the analysed age groups men declared more intensive physical activity than women of the same age. The differences between arithmetic means of the declared physical activity in all age groups are not statistically relevant.Conclusions: There is a necessity to search for effective programmes to promote physical activity and to create intervention programmes in order to improve the level of physical activity of elderly people.